Volitional qualities as individual success factor in team sports - Shagivaleeva, G. R.; Shterts, O. M.; Biserova, G. K. (Theory and Practice of Physical Culture, 2018)
Subject to analysis in the study were the individual volitional qualities and achievement motivations in modern team sports. Sports are ranked increasingly high by the modern communities, and athletes are expected to demonstrate a variety of personal qualities for success including willpower, determination, initiative, self-reliance, stress-tolerance and self-control to face challenges and demonstrate success in their sport careers. The empirical data mined in the study showed the athletes tested with high willpower being generally highly motivated for achievements, demonstrating great competitive spirit and striving to win. Objective of the study was to analyze individual volitional test rates versus achievement motivations in team sports. Subject to the study were junior athletes (n=60) whose individual volitional qualities and achievement motivations were tested. The study found age-specific variations in the volitional qualities and achievement motivations; and a data correlation analysis under the study demonstrated the volitional qualities being ranked among the key success factors in modern team sports. Significance of the statistical differences in the data arrays was rated by the Student t-criterion; and the Pearson's linear correlation coefficient was applied for the data correlation analysis.